DOES THE RESEMBLANCE BETWEEN A SNAKE, VIPER OR SERPENT EXIST? - Cerino Quevedo, Hugo Enrique; Barragán Vázquez, María del Rosario (Kuxulkab', 2023)
The frequent confusion in the use of the terms snake, viper or snake as if they were synonyms when respectively they are not, complicates the understanding of the need to clarify these distinctions to promote a coexistence between these reptiles and humans; despite being one of the least understood groups, they play a crucial role in the regulation of species populations and in the balance of natural ecosystems. This article highlights the main differences that allow the proper identification of these organisms.
Keywords: Ecosystems; Synonymy; Coexistence; Reptiles